High-Frequency Radar Observations of Surface Circulation Features along the South-Western Australian Coast - Simone Cosoli; Charitha Pattiaratchi; Yasha Hetzel (Journal of Marine Science and Engineering, 2020)
A new merged high-frequency radar (HFR) data set collected using SeaSonde and WERA (WEllen RAdar) systems was used to examine the ocean surface circulation at diurnal, seasonal and inter-annual time scales along the south-west coast of Australia (SWWA), between 29°−32° S. Merging was performed after resampling WERA data on the coarser SeaSonde HFR grid and averaging data from the two HFR systems in the area of common overlap. Direct comparisons between WERA and SeaSonde vectors in their overlapping areas provided scalar and vector correlation values in the range Ru = [0.24, 0.76]; Rv = [0.39, 0.83]; ρ = [0.44, 0.75], with mean bias between velocity components in the range [−0.02, 0.28] ms−1, [−0.16, 0.16] ms−1 for the U, V components, respectively. The lower agreement between vectors was obtained in general at the boundaries of the HFR domains, where the combined effects of the bearing errors, geometrical constraints, and the limited angular field of view were predominant. The combined data set allowed for a novel characterization of the dominant features in the region, such as the warmer poleward-flowing Leeuwin Current (LC), the colder Capes Current (CC) and its northward extensions, the presence of sub-mesoscale to mesoscale eddies and their generation and aggregation areas, along with the extent offshore of the inertial-diurnal signal. The contribution of tides was weak within the entire HFR domain (<10% total variance), whilst signatures of significant inertial- and diurnal-period currents were present due to diurnal−inertial resonance. A clear discontinuity in energy and variance distribution occurred at the shelf break, which separates the continental shelf and deeper offshore regions, and defined the core of the LC. Confined between the LC and the coastline, the narrower and colder CC current was a feature during the summer months. Persistent (lifespan greater than 1 day) sub-mesoscale eddies (Rossby number O (1)) were observed at two main regions, north and south of 31.5° S, offshore of the 200 m depth contour. The majority of these eddies had diameters in the range 10−20 km with 50% more counter clockwise rotating (CCW) eddies compared to clockwise (CW) rotating eddies. The northern region was dominated by CCW eddies that were present throughout the year whilst CW eddies were prevalent in the south with lower numbers during the summer months.